1929 Iowa Acts 90, § 30, Carrying Firearms in Motor Vehicles - (:unkn) unknown (My University, 1929)
Carrying Firearms in Motor Vehicles, § 30: Prohibited carry of a gun or any firearms in or on a motor vehicle.
Keywords: TRANSFER & POSSESSION